A nutritionist and an educator in professional horseracing: using reflection to create 'My process'. Issue 5 (3rd September 2017) - Martin, Daniel
Abstract: The present paper provides the reflective accounts of a practitioner as both a lecturer in further and higher education, and as a performance nutritionist within professional horseracing. Adopting a first-person writing style and through the use of creative non-fictional anecdotes, I share critical accounts 'in-action' that shaped my initial teaching philosophy and my introduction to horseracing. These shared events culminate in me questioning my initial approach to performance nutrition within the harsh and challenging sport of horseracing, and despite being contrasting vocations, how ideologies from education can be adopted into the practice of nutrition. I close by reflecting upon my reflections and my initial trepidations, however, go on to conclude that engaging in these processes acted as a tool to think critically, self-assess and develop my own practices.